Silicon steel crystallizer protection slag and preparation method thereof

By using the optimized mixer silicon steel crystal device to protect the residue in the high -pulling speed casting, the problem of lubrication and insufficient heat transfer caused by uneven protection of the residue residue has significantly improved the quality of the surface of the cast blank and the stability of the continuous casting process. Essence

CN118926495BActive Publication Date: 2025-01-28LENGSHUIJIANG GAOKE KILN REFRACTORY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411426588.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-28
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

During the high-pull speed continuous casting process, uneven viscosity of the protective slag leads to uneven lubrication and heat transfer between the crystallizer wall and the solidified blank shell, resulting in defects in the surface of the cast blank and the problem of steel leakage.

Method used

A silicon steel crystal device is used to protect the residue. Its composition includes calcium oxide, alumina, silicon oxide, carbonized rice shells, oxide, calcium fluoride, salt -containing coarse borax, spinelite, manganese oxide, carbonate and adhesion, bonding and bonding The agent can adjust the viscosity and performance of the protective residue by optimizing the ratio and preparation method.

Benefits of technology

By optimizing the ratio and preparation methods, ensure the uniform consumption of the protection of the residue and good lubrication and heat transfer performance, reduce the surface defects and the occurrence of bonding steel leakage steel, and improve the stability and product quality of the continuous casting process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118926495B_ABST
    Figure CN118926495B_ABST
Patent Text Reader

Abstract

The present invention discloses a silicon steel crystallizer protective slag and a preparation method thereof, and belongs to the field of protective slag. The silicon steel crystallizer protective slag comprises the following components by weight: calcium oxide: 20-25 parts, aluminum oxide: 4-8 parts, silicon dioxide: 30-40 parts, carbonized rice husk: 4-8 parts, rubidium oxide: 4-8 parts, calcium fluoride: 4-8 parts, salt-containing coarse borax: 1-2 parts, spinel: 1-2 parts, manganese oxide: 0.5-3 parts, barium carbonate: 0.5-1 parts, and adhesive: 1-3 parts. The production scheme of the present invention optimizes the ratio to ensure a certain melting rate while ensuring the thermal insulation effect, so that it has a certain liquid slag layer thickness, so that the protective slag is evenly consumed, thereby ensuring the smooth continuous casting process and producing high-quality ingots. When salt-containing coarse borax and spinel are added to the protective slag, the viscosity of the protective slag increases with the A1 in the slag. 2 O 3 The variation range of the content increase is small, therefore, the addition of salt-containing coarse borax and spinel in the present invention can properly adjust the viscosity of the protective slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to protective slag, and in particular to a silicon steel crystallizer protective slag and a preparation method thereof. Background Art

[0002] With the progress of science and technology, continuous casting technology has gradually matured. In recent years, continuous casting technology has been widely adopted by domestic and foreign steel enterprises. Continuous casting and rolling have been widely favored due to its simplified process, short production cycle, high yield rate, and suitability for producing products with heat instead of cold, and have broad development prospects. However, high-speed casting technology has also brought many new problems to the continuous casting process. The most important thing is that with the increase of continuous casting speed, the relative consumption of continuous casting functional protection materials decreases, which will cause uneven lubrication and heat transfer between the crystallizer wall and the solidified billet shell, which will lead to surface defects of the billet and even bonding and leakage, especially during the unstable continuous casting period.

[0003] In the continuous casting process, the selection of protective slag has an important influence on the performance of the protective slag. It should be noted that the viscosity of the continuous casting protective slag has an important influence on the metallurgical behavior occurring in the crystallizer, including the inflow and consumption of liquid slag, lubrication, and absorption of inclusions. In general, the protective slag is required to have certain heat transfer properties, good thermal insulation properties, good non-metallic absorption, good lubrication and stable performance. When the viscosity of the protective slag is too high, it is difficult to flow into the gap between the meniscus of the molten steel and the crystallizer. The protective slag film is thin and uneven, and the consumption is small, which can easily cause poor lubrication and heat transfer, and can cause longitudinal cracks in the broken shell. When the viscosity of the protective slag is too low, the protective slag film may be too thick, and the slag film thickness will also be uneven, lubrication and heat transfer will be uneven, and longitudinal cracks will increase. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a silicon steel crystallizer protective slag; another purpose of the present invention is to provide a method for preparing silicon steel crystallizer protective slag.

[0005] Technical solution: A silicon steel crystallizer protection slag, comprising the following components by weight: calcium oxide: 20-25 parts, aluminum oxide: 4-8 parts, silicon dioxide: 30-40 parts, carbonized rice husk: 4-8 parts, rubidium oxide: 4-8 parts, calcium fluoride: 4-8 parts, salt-containing coarse borax: 1-2 parts, spinel: 1-2 parts, manganese oxide: 0.5-3 parts, barium carbonate: 0.5-1 parts, and adhesive: 1-3 parts;

[0006] The preparation method of the silicon steel crystallizer protection slag is:

[0007] S1. Add 20% sulfuric acid aqueous solution to boron magnesium ore powder and mechanically stir to decompose it, slowly add sodium carbonate to neutralize it while stirring, and evaporate the water under reduced pressure at 70°C to obtain salt-containing crude borax;

[0008] S2, grinding and mixing calcium oxide, aluminum oxide, silicon dioxide, carbonized rice husk, rubidium oxide, calcium fluoride, salt-containing coarse borax, spinel, manganese oxide, and barium carbonate, and sifting through a 50-mesh sieve to obtain powder 1;

[0009] S3, adding a binder to the powder 1 obtained in step S1, stirring and mixing evenly to obtain irregular particles;

[0010] S4, crushing the irregular particles obtained in step S2, passing through a 50-mesh sieve, and obtaining powder 2;

[0011] S5, spray granulate the powder 2.

[0012] Preferably, the binder is cross-linked sodium carboxymethyl cellulose.

[0013] Preferably, the carbonized rice husk has a carbon content of ≥40% and a bulk density of 0.10-0.30 g / cm 3 Carbonized rice husk.

[0014] Preferably, the spinel is spinel powder.

[0015] Preferably, the melting temperature of the mold slag is 960°C to 1100°C, and the viscosity at 1300°C is 0.2 to 0.3 Pa﹒s.

[0016] Preferably, the basicity (CaO / SiO2) of the protective slag is 0.5-0.7.

[0017] Beneficial effects:

[0018] (1) The production scheme of the present invention optimizes the ratio to ensure the insulation effect while ensuring a certain melting rate, so that it has a certain liquid slag layer thickness, so that the protective slag is consumed evenly, thereby ensuring the smooth continuous casting process and producing high-quality ingots.

[0019] (2) When salt-containing coarse borax and spinel are added to the protective slag, the viscosity of the protective slag changes slightly with the increase of the A12O3 content in the slag. Therefore, the addition of salt-containing coarse borax and spinel in the present invention can appropriately adjust the viscosity of the protective slag.

[0020] (3) When the salt-containing coarse borax is added to the protective slag, the salt-containing coarse borax can react with some metal oxides, thereby dissolving some metal impurities and making the product quality higher. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a picture of the finished product of the protective slag of the present invention.

[0022] Figure 2 The figure is a schematic diagram of the reaction principle for preparing the salt-containing crude borax of the present invention.

[0023] Figure 3 This is a schematic diagram of the principle of removing metal oxides from salt-containing coarse borax of the present invention. DETAILED DESCRIPTION

[0024] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0025] Embodiment 1

[0026] A silicon steel crystallizer protection slag comprises the following components in percentage by weight: 20 parts of calcium oxide, 4 parts of aluminum oxide, 30 parts of silicon dioxide, 4 parts of carbonized rice husk, 4 parts of rubidium oxide, 4 parts of calcium fluoride, 1 part of salt-containing coarse borax, 1 part of spinel, 0.5 parts of manganese oxide, 0.5 parts of barium carbonate, and 1 part of binder. The binder is cross-linked sodium carboxymethyl cellulose.

[0027] Its preparation method is:

[0028] (1) Add 20% sulfuric acid aqueous solution to boron magnesium ore powder, stir mechanically to decompose it, slowly add sodium carbonate to neutralize it while stirring, and evaporate the water under reduced pressure at 70°C to obtain salt-containing crude borax;

[0029] (2) 20 kg of calcium oxide, 4 kg of aluminum oxide, 30 kg of silicon dioxide, 4 kg of carbonized rice husk, 4 kg of rubidium oxide, 4 kg of calcium fluoride, 1 kg of the salt-containing crude borax obtained in step (1), 1 kg of spinel, 0.5 kg of manganese oxide, and 0.5 kg of barium carbonate were crushed and mixed uniformly by an ultrafine grinder, and passed through a 50-mesh sieve to obtain powder 1;

[0030] (3) adding a binder to the powder 1 obtained in step (2) and stirring and mixing the mixture to obtain irregular particles;

[0031] (4) The irregular particles obtained in step (3) are crushed by an ultrafine grinder and passed through a 50-mesh sieve to obtain powder 2;

[0032] (5) The powder 2 is sprayed and granulated. The obtained mold slag product is as follows: Figure 1 shown.

[0033] Embodiment 2

[0034] A silicon steel crystallizer protection slag comprises the following components in percentage by weight: 23 parts of calcium oxide, 6 parts of aluminum oxide, 35 parts of silicon dioxide, 6 parts of carbonized rice husk, 6 parts of rubidium oxide, 6 parts of calcium fluoride, 1.5 parts of salt-containing coarse borax, 1.5 parts of spinel, 2 parts of manganese oxide, 0.7 parts of barium carbonate, and 2 parts of binder. The binder is cross-linked sodium carboxymethyl cellulose.

[0035] Its preparation method is:

[0036] (1) Add 20% sulfuric acid aqueous solution to boron magnesium ore powder, stir mechanically to decompose it, slowly add sodium carbonate to neutralize it while stirring, and evaporate the water under reduced pressure at 70°C to obtain salt-containing crude borax;

[0037] (2) 23 kg of calcium oxide, 6 kg of aluminum oxide, 35 kg of silicon dioxide, 6 kg of carbonized rice husk, 6 kg of rubidium oxide, 6 kg of calcium fluoride, 1.5 kg of the salt-containing crude borax obtained in step (1), 1.5 kg of spinel, 2 kg of manganese oxide, and 0.7 kg of barium carbonate were crushed and mixed uniformly by an ultrafine grinder, and passed through a 50-mesh sieve to obtain powder 1;

[0038] (3) adding a binder to the powder 1 obtained in step (2) and stirring and mixing the mixture to obtain irregular particles;

[0039] (4) The irregular particles obtained in step (3) are crushed by an ultrafine grinder and passed through a 50-mesh sieve to obtain powder 2;

[0040] (5) The powder 2 is sprayed and granulated. The obtained mold slag product is as follows: Figure 1 shown.

[0041] Embodiment 3

[0042] A silicon steel crystallizer protection slag comprises the following components in percentage by weight: calcium oxide: 25 parts, aluminum oxide: 8 parts, silicon dioxide: 40 parts, carbonized rice husk: 8 parts, rubidium oxide: 8 parts, calcium fluoride: 8 parts, salt-containing coarse borax: 2 parts, spinel: 2 parts, manganese oxide: 3 parts, barium carbonate: 1 part, and a binder: 3 parts. The binder is cross-linked sodium carboxymethyl cellulose.

[0043] Its preparation method is:

[0044] (1) Add 20% sulfuric acid aqueous solution to boron magnesium ore powder, stir mechanically to decompose it, slowly add sodium carbonate to neutralize it while stirring, and evaporate the water under reduced pressure at 70°C to obtain salt-containing crude borax;

[0045] (2) 25 kg of calcium oxide, 8 kg of aluminum oxide, 40 g of silicon dioxide, 8 kg of carbonized rice husk, 8 kg of rubidium oxide, 8 kg of calcium fluoride, 2 kg of the salt-containing crude borax obtained in step (1), 2 kg of spinel, 3 kg of manganese oxide, and 1 kg of barium carbonate were crushed and mixed uniformly by an ultrafine pulverizer, and then sieved through a 50-mesh sieve to obtain powder 1;

[0046] (3) adding a binder to the powder 1 obtained in step (2) and stirring and mixing the mixture to obtain irregular particles;

[0047] (4) The irregular particles obtained in step (3) are crushed by an ultrafine grinder and passed through a 50-mesh sieve to obtain powder 2;

[0048] (5) The powder 2 is sprayed and granulated. The obtained mold slag product is as follows: Figure 1 shown.

[0049] Comparative Example 1

[0050] A silicon steel crystallizer protection slag comprises the following components in percentage by weight: 20 parts of calcium oxide, 4 parts of aluminum oxide, 30 parts of silicon dioxide, 4 parts of rubidium oxide, 4 parts of calcium fluoride, 1 part of salt-containing coarse borax, 1 part of spinel, 0.5 parts of manganese oxide, 0.5 parts of barium carbonate, and 1 part of binder, wherein the binder is cross-linked sodium carboxymethyl cellulose.

[0051] Its preparation method is:

[0052] (1) Add 20% sulfuric acid aqueous solution to boron magnesium ore powder, stir mechanically to decompose it, slowly add sodium carbonate to neutralize it while stirring, and evaporate the water under reduced pressure at 70°C to obtain salt-containing crude borax;

[0053] (2) 20 kg of calcium oxide, 4 kg of aluminum oxide, 30 kg of silicon dioxide, 4 kg of rubidium oxide, 4 kg of calcium fluoride, 1 kg of the salt-containing crude borax obtained in step (1), 1 kg of spinel, 0.5 kg of manganese oxide, and 0.5 kg of barium carbonate were crushed and mixed uniformly by an ultrafine grinder, and passed through a 50-mesh sieve to obtain powder 1;

[0054] (3) adding a binder to the powder 1 obtained in step (2) and stirring and mixing the mixture to obtain irregular particles;

[0055] (4) The irregular particles obtained in step (3) are crushed by an ultrafine grinder and passed through a 50-mesh sieve to obtain powder 2;

[0056] (5) The powder 2 is sprayed and granulated.

[0057] Comparative Example 2

[0058] A silicon steel crystallizer protection slag comprises the following components in percentage by weight: 20 parts of calcium oxide, 4 parts of aluminum oxide, 30 parts of silicon dioxide, 4 parts of carbonized rice husk, 4 parts of calcium fluoride, 1 part of salt-containing coarse borax, 1 part of spinel, 0.5 parts of manganese oxide, 0.5 parts of barium carbonate, and 1 part of binder, wherein the binder is cross-linked sodium carboxymethyl cellulose.

[0059] Its preparation method is:

[0060] (1) Add 20% sulfuric acid aqueous solution to boron magnesium ore powder, stir mechanically to decompose it, slowly add sodium carbonate to neutralize it while stirring, and evaporate the water under reduced pressure at 70°C to obtain salt-containing crude borax;

[0061] (2) 20 kg of calcium oxide, 4 kg of aluminum oxide, 30 kg of silicon dioxide, 4 kg of carbonized rice husk, 4 kg of calcium fluoride, 1 kg of salt-containing coarse borax, 1 kg of spinel, 0.5 kg of manganese oxide, and 0.5 kg of barium carbonate were crushed and mixed uniformly by an ultrafine pulverizer, and then sieved through a 50-mesh sieve to obtain powder 1;

[0062] (3) adding a binder to the powder 1 obtained in step (2) and stirring and mixing the mixture to obtain irregular particles;

[0063] (4) The irregular particles obtained in step (3) are crushed by an ultrafine grinder and passed through a 50-mesh sieve to obtain powder 2;

[0064] (5) The powder 2 is sprayed and granulated.

[0065] Comparative Example 3

[0066] A silicon steel crystallizer protection slag comprises the following components in percentage by weight: 20 parts of calcium oxide, 4 parts of aluminum oxide, 30 parts of silicon dioxide, 4 parts of carbonized rice husk, 4 parts of rubidium oxide, 4 parts of calcium fluoride, 1 part of spinel, 0.5 parts of manganese oxide, 0.5 parts of barium carbonate, and 1 part of binder, wherein the binder is cross-linked sodium carboxymethyl cellulose.

[0067] Its preparation method is:

[0068] (1) 20 kg of calcium oxide, 4 kg of aluminum oxide, 30 kg of silicon dioxide, 4 kg of carbonized rice husk, 4 kg of rubidium oxide, 4 kg of calcium fluoride, 1 kg of spinel, 0.5 kg of manganese oxide, and 0.5 kg of barium carbonate were crushed and mixed uniformly by an ultrafine grinder, and then sieved through a 50-mesh sieve to obtain powder 1;

[0069] (2) adding a binder to the powder 1 obtained in step (1) and stirring and mixing the mixture to obtain irregular particles;

[0070] (3) The irregular particles obtained in step (2) are crushed by an ultrafine grinder and passed through a 50-mesh sieve to obtain powder 2;

[0071] (4) The powder 2 is sprayed and granulated.

[0072] The silicon steel mold protection slag obtained in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and its melting temperature was tested by heating and melting method; the viscosity after melting was tested by rotating cylinder method using rotational viscometer, and calculated by formula η=Κ•Δθ, where η is the viscosity of the solution to be tested, K is the instrument constant, Δθ is the annual torsion angle change of the probe in the air and in the solution to be tested; basicity is the ratio of silicon dioxide to calcium oxide; through pilot production, the surface quality defects of silicon steel produced by different protection slags were observed to test its surface quality defects. The test results are shown in Table 1.

[0073] Table 1 Test results of protective slag of the embodiment and the comparative example

[0074]

[0075] It can be seen from the results in Table 1 that the silicon steel mold protection slag prepared by the present invention can improve the viscosity to a greater extent through the cooperation of various components, and also has a good effect on improving the surface quality defects of steel.

[0076] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A silicon steel mold protection slag, characterized in that: The invention comprises the following components by weight: calcium oxide: 20-25 parts, aluminum oxide: 4-8 parts, silicon dioxide: 30-40 parts, carbonized rice husk: 4-8 parts, rubidium oxide: 4-8 parts, calcium fluoride: 4-8 parts, salt-containing coarse borax: 1-2 parts, spinel: 1-2 parts, manganese oxide: 0.5-3 parts, barium carbonate: 0.5-1 parts, and adhesive: 1-3 parts; The preparation method of the silicon steel crystallizer protection slag is: S1. Add 20% sulfuric acid aqueous solution to boron magnesium ore powder and mechanically stir to decompose it, slowly add sodium carbonate to neutralize it while stirring, and evaporate the water under reduced pressure at 70°C to obtain salt-containing crude borax; S2, grinding and mixing calcium oxide, aluminum oxide, silicon dioxide, carbonized rice husk, rubidium oxide, calcium fluoride, the salt-containing crude borax obtained in step S1, spinel, manganese oxide, and barium carbonate, and sifting through a 50-mesh sieve to obtain powder 1; S3, adding a binder to the powder 1 obtained in step S2, stirring and mixing evenly to obtain irregular particles; S4, crushing the irregular particles obtained in step S3, passing through a 50-mesh sieve, and obtaining powder 2; S5, spray granulate the powder 2.

2. The silicon steel mold protection slag according to claim 1, characterized in that: The binder is cross-linked sodium carboxymethyl cellulose.

3. The silicon steel mold protection slag according to claim 1, characterized in that: The carbonized rice husk has a carbon content of ≥40% and a bulk density of 0.10-0.30 g / cm 3 Carbonized rice husk.

4. The silicon steel mold protection slag according to claim 1, characterized in that: The spinel is spinel powder.

5. The silicon steel mold protection slag according to claim 1, characterized in that: The melting temperature of the mold slag is 960°C to 1100°C, and the viscosity at 1300°C is 0.2 to 0.3 Pa﹒s.

6. The silicon steel mold protection slag according to claim 1, characterized in that: The basicity (CaO / SiO2) of the protective slag is 0.5~0.7.

Citation Information

Patent Citations

  • Low-reactivity covering slag and preparation method thereof

    CN106270429A

  • Mold flux for continuous casting and continuous casting method

    CN108348992A